Factors influencing willingness to communicate in English among EFL Iranian PhD students in a public university in Malaysia - Saadat, Uranus (2018)
Willingness to Communicate (WTC) in the second language (L2) has received substantial consideration in modern language research and instruction. L2 learners with higher L2 WTC are more likely to use L2 in authentic communication and facilitate their learning. Previously, studies mostly investigated L2 WTC in the same contexts where L2 learners live. However, there is still a demand to obtain information through qualitative method to know how L2 WTC could be changed among EFL students when they move to a new foreign context where English is an L2. This study intends to investigate how oral L2 WTC of a group of EFL Iranian PhD students in a public university in Malaysia has changed during their stay in this country and what factors have resulted in their changes. To conduct this study, a qualitative case study method was implemented to obtain information from 8 participants through the semi-structured interview as the main method, followed by focus group discussion and solicited diaries of the participants. This study was guided by four research questions: 1) what were the EFL Iranian PhD students’ perceptions about the factors influencing their trait-like L2 WTC orally when they were living in Iran, before coming to Malaysia? 2) What were the EFL Iranian PhD students’ perceptions about the factors influencing their trait-like L2 WTC orally after they moved to Malaysia? 3) What were the EFL Iranian PhD students’ perceptions about the factors influencing their situational L2 WTC orally in Malaysian context? 4) How did the participants self-evaluate their L2 WTC and L2 oral communication changes since they moved to Malaysia? The analyses of the data derived from the first research question yielded five major themes, namely: lack of exposure to L2 oral communication, cultural values, low L2 self-confidence, L2 extrinsic motivation, and enabling behaviours. Analysis of the second research question revealed six major themes, namely: raised awareness, cultural background, personality, exposure to L2 oral communication, extrinsic L2 motivation, and Increased L2 self-confidence. The third research question analysis indicated two major interrelated themes as interactional factors and affective factors. The last research question resulted in three major themes, namely: increased stable L2 WTC; unsolved issues of situational L2 WTC; and inadequate satisfaction with L2 oral communication improvement. The findings indicated that the rare exposure to the English language in Iran had resulted in its little practice in authentic settings and low L2 WTC among the respondents before coming to Malaysia. Moreover, the respondents suffered from deficiencies in English oral communication when they arrived in Malaysia although they had got an IELTS band score required for the university entrance and participated in English classes in Iran. However, by understanding their problems in L2 oral communication and its importance for their academic success in Malaysia, they gradually changed their attitude toward it, increased their L2 WTC and improved L2 oral communication. This study also provides theoretical and practical implications for designing teaching methods to maximize language learners’ L2 WTC in the classroom which leads to their L2 oral communication improvement.